The crisis of social reproduction and therapeutic self-care - Salmenniemi, Suvi (SAGE Publications, 2026)
The article examines therapeutic self-care as a practice of social reproduction. It argues that therapeutic self-care sits at the heart of the systemic crisis materialising from the contradicting logics between capital accumulation and social reproduction. The article contributes to social reproduction feminism by showing the centrality of therapeutic self-care for reproducing capacity to labour and maintaining life as such. It also contributes to scholarship on therapeutic culture by offering a materialist reading and showing how capitalist production relies on and exploits self-care. It argues that therapeutic self-care has gained particularly heightened importance for social reproduction in the current capitalist conjuncture due to neoliberal reconfiguration of the welfare state, which shifts responsibility for social reproduction to individuals, and to the post-Fordist work ethic, which emphasises personality and subjectivity as pivotal factors of production. Therapeutic self-care intensifies the crisis of social reproduction through optimising workers for exploitation, but also offers potential to resistance, allowing workers to withdraw from work society and refuse to reproduce themselves as commodity labour power. However, such resistance tends to be individualised, reflecting structural barriers to collective struggles. The article concludes that new ways of political organising are sorely needed to radically reconfigure the dynamics between productive and reproductive forces, fight disenfranchisement and translate individualised forms of resistance into collective political struggles.